SEMIOTIC STUDY OF DOCUMENTARY THE EXISTENCE AGRICULTURAL AND AGRICULTURAL INDUSTRY OF CELUK BURUAN VILLAGE - Setiawan, I Nyoman Anom Fajaraditya; Adnyana, I Nyoman Widhi; Aditama, Putu Wirayudi (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2020)
The culture of farming has become a part of life in Bali and this has become a part of popular economic activity. This phenomenon is recorded in the documentary of the existence of agriculture and the Celuk Buruan agricultural industry and has become a fact of circumstances in the current era of change. In the film, of course, there is the production of signs in the visualization and these signs hide the intention behind the facts. In addition to matters of agriculture, the agricultural industry that lives from the surrounding agriculture also has an impact on the changes that occur. So whatever happens in these two fields will also impact the lower level economy. The existence of a series of signs, it is necessary to explore the motivation behind the actual story. This is interpreted qualitatively interpretatively in the analysis of the sign based on the point of view that appears in the film. The study of documents by watching films and the current situation brings back a pattern outside the implied. Agriculture, development, and change are sure signs to follow and play a role in changing the mindset of the phenomena in this documentary.